HATE SPEECH AS A CHALLENGE FOR MODERN SOCIETIES: INTERNATIONAL LEGAL ASPECT - Syroid, Tetyana (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2025)
The article explores the issue of hate speech in the context of security challenges for human rights and societies as a whole. It focuses on the factors that exacerbate the spread of hate speech in societies, including risk situations (pandemics, natural disasters), economic instability, armed conflicts, internal political upheavals, etc. The study highlights the tools facilitating the dissemination of hate speech, thereby contributing to unlawful actions, particularly the use of information and communication technologies, the internet, social media, and various broadcasting platforms. The article identifies vulnerable groups in any society that are most at risk from hate speech (representatives of national minorities, LGBTQ communities, women, migrants, etc.) and emphasizes the negative impact of hate speech on young people and adolescents, which will have consequences for society as a whole. Since young people form the demographic foundation of any state, governments must foster the development of a future society based on respect for diversity and the recognition of human dignity as the highest value. The study provides a consolidated definition of hate speech in accordance with universal and regional international instruments and presents the relevant case law of the European Court of Human Rights. It outlines measures to counter hate speech implemented at the level of international intergovernmental organizations (UN, Council of Europe, European Union, OSCE), specialized agencies and institutions (UNESCO, EU Agency for Fundamental Rights, Office for Democratic Institutions and Human Rights). These measures include legal and political actions, awareness-raising and educational initiatives, media engagement, and support for victims. Relevant conclusions and recommendations are provided.